DESAIN DAN UJI COBA MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI POWTOON SEBAGAI SUMBER BELAJAR PADA MATERI SISTEM PERIODIK UNSUR - Nurul Latifah; Lazulva Lazulva (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This research was instigated by the lack of variative learning media in learning process. This research aimed at knowing the level of validity and practicality of Powtoon animation media on Element periodic system lesson. It was a Research and Development with 4-D (Define, Design, Development, Disseminate) model. It was conducted at State Senior High School 09 Pekanbaru. The subject of this research were the expert of powtoon animation video design, learning lesson expert, chemistry teachers, and students at State Senior High School 09 Pekanbaru. The Object of this research were Powtoon animation video on element periodic system. It was primier data that was obtained from the questionnaire. Questionnaire of validity test and questionnaire of practicality test were the instruments of collecting the data. Data was analyzed by using analysis of descriptive and quantitative descriptive techniques. The Powtoon animation video media was tested with the percentage 88.35% (Very valid) and practice 86.54% (Very practice). From the result, it could be concluded that Powtoon animation video media on Element priodic system lesson was valid and practice and appropriate to be as an additional media in learning process